ANALYSIS OF THE MAIN TECHNICAL INDICATORS OF CORN, WHEAT AND SUNFLOWER CROPS AT THE LEVEL OF THE EUROPEAN UNION - Mariana POSTAMENTEL; Cătălina-Nicoleta COMAN (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The content of this paper aims to analyze the main technical indicators of three of the most important crops in the European Union, namely corn, wheat and sunflower. By interpreting the statistical data provided by Eurostat on the cultivated area, the total production and the average production of the three crops mentioned above using the trend, the standard deviation and the coefficient of variation, an analysis of the Member States of the European Union will be carried out in order to determine which of them dominates the crop sector of corn, wheat and sunflower, in the end to figure out that not one of the analised Member States can be called the leader regarding the agricultural sector, because the results are so different beeing influenced by so many external factors.